Diversidade bacteriana em cavidade oral e retal de mico-leão-preto Leontopithecus chrysopygus (Mikan, 1823) - Fatoretto, Bruna Talita (2019)
The black lion tamarin, Leontopithecus chrysopygus is an endangered primate species, restricted to fragments of the Atlantic Forest in the State of São Paulo, Brazil. Information on microbiology, epidemiology and pathogens transmission are scarce and the aim of this study was to describe the bacterial diversity in the oral and rectal cavities of free-ranging (in situ) and captive (ex situ) animals. For identification of bacterial isolates, we used Matrix-assisted laser desorption / ionization time-of-flight mass spectrometry (MALDI-TOF), Gram stain and Polymerase Chain Reaction (PCR). A total of 249 bacterial isolates were studied and the results revealed a different profile of bacterial diversity between in situ and ex situ animals. In total, 19 bacteria genera were found and the most frequent genera in captive animals were: Escherichia, Neisseria, Streptococcus, Proteus, Enterobacter; and in free-ranging animals were: Bacillus, Staphylococcus, Enterococcus and Pseudomonas. There are no reports in the literature regarding the identification of Cronobacter sp., Delftia sp., Kocuria sp., Lysinibacillus sp., Neisseria sp., Paenibacillus sp. in Leontopithecus chrysopygus, which are presented in this study for the first time. Bacterial with pathogenic potential were found and this work demonstrated the importance of identifying these microorganisms for future management and conservation practices.